Biomechanical comparison of the four-strand cruciate and Strickland techniques in animal tendons (Clinics, 2013)
OBJECTIVE: The objective of this study was to compare two four-strand techniques: the traditional Strickland and cruciate techniques. METHODS: Thirty-eight Achilles tendons were removed from 19 rabbits and were assigned to two groups based on suture technique (Group 1, Strickland suture; Group 2, cruciate repair). The sutured tendons were subjected to constant progressive distraction using a universal testing machine (Kratos®). Based on data from the instrument, which were synchronized with the visualized gap at the suture site and at the time of suture rupture, the following data were obtained: maximum load to rupture, maximum deformation or gap, time elapsed until failure, and stiffness. RESULTS: In the statistical analysis, the data were parametric and unpaired, and by Kolmogorov-Smirnov test, the sample distribution was normal. By Student's t-test, there was no significant difference in any of the data: the cruciate repair sutures had slightly better mean stiffness, and the Strickland sutures had longer time-elapsed suture ruptures and higher average maximum deformation. CONCLUSIONS: The cruciate and Strickland techniques for flexor tendon sutures have similar mechanical characteristics in vitro.